Latest Oligocene adakitic rocks in western Iran: implications for early crustal thickening and tectonic evolution of the Iran Block. Issue 1 (2023) - Liu, Yi-Xin; Chen, Jian-Lin; Yang, Tian-Nan; Hou, Zeng-Qian; Zhang, Hong-Rui; Yang, Zhi-Ming; Yang, Zhu-Sen; Aghazadeh, Mehraj; Xu, Ji-Feng
No abstract available